Drechslera rostrata a new mycoparasite of Syncephalastrum racemosum - K. N. Pandey; R. C. Gupta (Acta Mycologica, 2014)
Drechslera rostrata is reported here as a new mycoparasite of Syncephalastrum racemosum.